(untitled) (Boca Raton, Fla., 1980)
The purpose of this chapter on enzyme immobilization is to introduce the reader to the diversity of immobilization techniques available and some of the variables that affect the actual immobilization procedures.
Keywords: Immobilized enzymes,Enzyme cố định; Industrial applications,Ứng dụng công nghiệp